Letter : Spanish War - Holmes, Walter M.
012a-0113-001 Telephone TERMINUS 3913 Telegraphic Address NATAGRIC, KINCROSS, LONDON. NATIONAL UNION OF AGRICULTURAL WORKERS AFFILIATED TO TRADES UNION CONGRESS AND THE LABOUR PARTY APPROVED SOCIETY UNDER NATIONAL INSURANCE ACT REGISTERED No.395. General Secretary: W. HOLMES To whom all communications should be addressed Registered Office HEADLAND HOUSE, 308 GRAYS INN ROAD, LONDON W.C.1 In your reply please quote............. 15 Somerset Road Tottenham N.17. Sir Walter Citrine Spanish War. Dear Sir In reply to your letter upon the above subject. I entirely agree with your suggestion that an interview be sought with Lord Halifax to discuss with him the question of the embargo upon the Spanish Governments efforts to secure arms. Yours faithfully W. Holmes 292/946/12a/113